The effects of EMG biofeedback therapy and facial nerve mobilization in Bell’s palsy - Sridharan, Padmapriya; Suganthirababu, Prathap; Srinivasan, Vignesh (International Journal of Research in Medical Sciences, 2026)
Background: Bell’s palsy is a common neurological disorder characterized by sudden, unilateral facial nerve paralysis, leading to both functional impairments and cosmetic concerns. While conventional treatment approaches are frequently employed to alleviate symptoms, emerging rehabilitation techniques such as electromyographic (EMG) biofeedback and facial nerve mobilization have shown promising potential in enhancing recovery outcomes. This study aimed to evaluate the combined effects of EMG biofeedback therapy and facial nerve mobilization on facial symmetry and functional recovery in patients with acute Bell’s palsy. Methods: A total of 30 participants, aged 18–40 years, with unilateral Bell’s palsy classified as Grade III–V on the Modified House–Brackmann (HB) Scale were recruited. Participants were allocated into two groups: the experimental group (n=15) received EMG biofeedback and facial nerve mobilization, whereas the conventional group (n=15) underwent traditional physiotherapy. Both groups participated in 45-minute treatment sessions, five days per week, for four weeks. Outcome measures included the Sunnybrook Facial Grading Scale (SFGS) and surface electromyography (sEMG). Results: Statistical analysis revealed significant improvements within both groups; however, the experimental group demonstrated greater gains. SFGS scores improved significantly within groups (p<0.001), with the experimental group achieving superior results (p<0.001) and a large effect size (r=–0.854). Surface EMG analysis indicated significantly higher post-treatment muscle activation across all facial muscles in the experimental group (p < 0.001). Conclusions: These findings suggest that EMG biofeedback combined with facial nerve mobilization is an effective intervention for enhancing facial symmetry and functional recovery in acute Bell’s palsy, making it a promising addition to rehabilitation protocols.